Price sensitivity testing as a basic tool for strategic pricing decisions - Kintler Jakub; Remeňová Katarína; Kmety Barteková Mária (Strategic Management, 2023)
Background: Data-driven decisions in each functional area of management, through all of the strategic levels, in the present time of dynamic changes in geopolitical and market conditions are necessary to achieve corporate (economic and social) goals, in line with securing future business success and sustainability. Because of this business need, we will focus in our research paper on price management, which can be seen as a supportive tool for strategic decisions, where competent decisions should be based on data-driven pricing decisions. Purpose: The aim of the research study is to identify what price consumers are prepared to pay for a new food product in a relatively saturated foreign market. The research study was conducted in the milk chocolate bar market segment. Study design: We applied the van Westendorp price sensitivity test to identify the range of acceptable prices for a product that is willing to enter a new foreign market. For this purpose, we used a milk chocolate bar product currently unknown in the Slovak market. Findings: In addition to the van Westendorp price sensitivity measurement, we used a non-parametric Mann Whitney U test to confirm the hypothesis that chocolate tasting will increase the likelihood of customers to pay a higher price for the tested product. The hypothesis mentioned above was statistically confirmed. Limitations: It is necessary to monitor customer reactions to a given price level and be prepared to optimize it. We did not address this part of the analysis in identifying a price that would be acceptable to consumers in terms of value perception, due to the scope of the study.